A retrospective case-control study to evaluate the use of beta-lactam desensitization in the management of penicillin-allergic patients: a potential strategy for Antimicrobial Stewardship Programs - Rodríguez-Alarcón, Alicia; Sanz de Mena, Manuela; Alanti, Soukaina Sara; Echeverría-Esnal, Daniel; Sorli, Luisa; Sendra, Elena; Benítez-Cano, Adela; Membrilla, Estela; Cots, Francesc; Güerri-Fernández, Robert; Adalia, Ramón; Horcajada, Juan Pablo; et al. (Frontiers in Pharmacology, 2023)
Introduction: Penicillin allergy labels (PAL) are common in the hospital setting and are associated with worse clinical outcomes. Desensitization can be a useful strategy for allergic patients when alternative options are suboptimal or not available. The aim was to compare clinical outcomes of patients with PAL managed with antibiotic desensitization vs. those who received alternative non-beta-lactam antibiotic treatments. Methods: A retrospective 3:1 case-control study was performed between 2015-2022. Cases were adult PAL patients with infection who required antibiotic desensitization; controls were PAL patients with infection managed with an alternative antibiotic treatment. Cases and controls were adjusted for age, sex, infection source, and critical or non-critical medical services. Results: Fifty-six patients were included: 14 in the desensitization group, 42 in the control group. Compared to the control group, desensitized PAL patients had more comorbidities, with a Charlson index (7.4 vs. 5; p=0.00) and more infections caused by multidrug-resistant (MDR) pathogens (57.1% vs. 28.6%; p=0.05). Thirty-day mortality was 14.3% in the desensitized group, 28.6% in the control group (p=0.24). Clinical cure occurred in 71.4% cases and 54.8% controls (p=0.22). Four control patients selected for MDR strains after alternative treatment; selection of MDR strains did not occur in desensitized patients. Five controls had antibiotic-related adverse events, including Clostridioides difficile or nephrotoxicity. No antibioticrelated adverse events were found in the study group. In multivariate analysis, no differences between groups were observed for main variables. Conclusion: Desensitization was not associated with worse clinical outcomes, despite more severe patients in this group. Our study suggests that antibiotic desensitization may be a useful Antimicrobial Stewardship tool for the management of selected PAL patients.